2006
DOI: 10.1111/j.1525-1438.2006.00541.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of survivin, PTEN and p27 in normal, hyperplastic, and carcinomatous endometrium

Abstract: We aimed to investigate if expressions of survivin and p27 proteins are involved in the development of endometrioid carcinoma, along with whether there are any correlations between these proteins and loss of wild-type PTEN that is found in up to 80% of endometrial carcinomas. We also studied their correlations with classical prognostic factors and survival in endometrial carcinoma. To our knowledge, this is the first time survivin expression is investigated in endometrial hyperplasia along with endometrioid ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
42
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 29 publications
9
42
0
1
Order By: Relevance
“…This suggests that survivin overexpression is selective toward high-grade, poorly differentiated tumors. This finding is consistent with reverse transcriptase PCR and immunohistochemistry data from other laboratories (Lehner et al, 2002;Takai et al, 2002;Erkanli et al, 2006Erkanli et al, , 2007.…”
supporting
confidence: 82%
“…This suggests that survivin overexpression is selective toward high-grade, poorly differentiated tumors. This finding is consistent with reverse transcriptase PCR and immunohistochemistry data from other laboratories (Lehner et al, 2002;Takai et al, 2002;Erkanli et al, 2006Erkanli et al, , 2007.…”
supporting
confidence: 82%
“…In normal control epithelium, represented by the control group, survivin protein was absent in all specimens. This was consistent with pu bli shed p ap ers sho win g the lack o f survivin immunoreactivity in normal adult tissues 43) . The present study found the survivin expression rate was 30 % (24/80) in the oral mucosal dysplasia, and it was 57.1 % (12 / 21) in oral squamous cell carcinoma.…”
Section: Discussionsupporting
confidence: 71%
“…In vivo, C. parvum appears to replicate in the basal crypt cells (52), and parasite development has a significant preference for mitotic cells in S/G 2 /M phase cells (65). Survivin also has a role in cell cycle progression (1,6,34), and its expression is controlled by cell cycle pathway components such as Myc and PTEN that are active only in the undifferentiated cells (12,19). If C. parvum can turn on survivin to manage apoptosis, it is also possible that this same mechanism operates to lock the host cell in a relatively undifferentiated state.…”
Section: Discussionmentioning
confidence: 99%